Memahami Penelitian Kualitatif dalam Akuntansi - Zul Azmi; Abdillah Arif Nasution; Wardayani wardayani (Department of Accounting-Faculty of Economic and Business (FEB), 2018)
This paper aims to describe qualitative research that began to develop in the field of accounting. Qualitative descriptive method is used to collect data and describe qualitative research in accounting. The results of research can add to the understanding of qualitative research in accounting. Qualitative research provides freedom from the limit of the deductive hypothesis testing obsession that allows to investigate issues and questions that have been neglected by the dominant research paradigm. Assimilating accounting disciplines with other disciplines may open up opportunities for qualitative research.